Motivational interviewing with community-dwelling older adults after hip fracture (MIHip): protocol for a randomised controlled trial. Issue 6 (9th June 2021) - Taylor, Nicholas F; O'Halloran, Paul D; Watts, Jennifer J; Morris, Rebecca; Peiris, Casey L; Porter, Judi; Prendergast, Luke A; Harding, Katherine E; Snowdon, David A; Ekegren, Christina L; Hau, Raphael; Mudiyanselage, Shalika B; et al.
Abstract : Introduction: Community-dwelling people recovering from hip fracture have the physical capacity to walk in their community but lack the confidence to do so. The primary aim of this trial is to determine whether motivational interviewing increases time spent walking at 12 months in community-dwelling people after hip fracture compared with an attention placebo control group. Secondary aims are to evaluate cost effectiveness, patient and health service outcomes and to complete a process evaluation. Methods and analysis: An assessor-blinded parallel group randomised controlled design with embedded health economic evaluation and process evaluation will compare the effects of n=270 participants randomly allocated to an experimental group (motivational interviewing) or a control group (dietary advice). For inclusion, participants are aged ≥65 years, living at home independently within 6 months of discharge from hospital after hip fracture and able to walk independently and communicate with conversational English. Key exclusion criteria are severe depression or anxiety, impaired intellectual functioning and being medically unstable to walk. Participants allocated to the experimental group will receive 10 (8 weekly and 2 booster) telephone-based sessions of motivational interviewing to increase walking over 16 weeks. Participants allocated to the control group will receive an equivalent dose of telephone-based dietary advice. The primary outcome is daily time spent walking over 7 days assessed at weeks 0, 9, 26 and 52. Secondary outcomes include measures of psychological-related function, mobility-related function, community participation, health-related quality of life and falls. Health service utilisation and associated costs will be assessed. Process evaluation will assess the fidelity of the motivational interviewing intervention and explore contextual factors through semistructured interviews. Ethics and dissemination: Ethical approval obtained from Eastern Health (E19-002), Peninsula Health (50261/EH-2019), Alfred Health (617/20) and La Trobe University (E19/002/50261). The findings will be disseminated in peer-reviewed journals, conference presentations and public seminars. Trial registration number: ACTRN12619000936123.